The Design and Application of In-depth Interview in Primary Care Research - XU Zhijie, WANG Yang, QIAN Yi (Zhongguo quanke yixue, 2024)
In-depth interview is to understand the life experience and lifestyle of a certain social group through in-depth conversation with the respondents, explore the formation process of specific phenomena, and propose ideas and recommendations to solve problems. In-depth interview has been widely used in the study of primary care research. Thus, understanding its basic concept and mastering the design and application process are essential to master this method. This paper comprehensively describes the research process of in-depth interview research according to the 3 stages at before, during and after the research. Before formally conducting in-depth interview research, researchers need to understand its basic concepts, characteristics and limitations related to the research purpose and process, and identify which studies are applicable. In the design and implementation of in-depth interview research, researchers should focus on the main steps of the research in four stages: recruitment of interviewees, design and modification of interview guide, collection of interview data, and analysis of interview data. After completing the data analysis of the in-depth interview, researchers need to write a research paper referring to the report specification of qualitative research to increase the credibility of research results and the transparency of the research process. In addition, this paper recommends five fields suitable for in-depth interviews in primary care research, and introduces learning resources for researchers to master in-depth interview methods. Through the introduction of in-depth interview research method, this paper aims to help researchers in the field of general practice/primary care to master a method suitable for scientific research, and provide methodology reference for improving the quality of qualitative research in this field in China.